A Six-Month Study of Pulmonary Cancer in Albanian Women. (4th March 2013) - Nikolla, Jolanda; Nanushi, Milda; Vyshka, Gentian; Hafizi, Hasan
Abstract : Lung cancer is a potentially lethal disease, whose prevalence in Albania is constantly increasing, especially in women. Early diagnosis is extremely important with regard to life expectancy and quality. The authors conducted a survey on the behaviour in a sample group of Albanian women diagnosed with primary and secondary lung cancers. A discussion upon diagnostic methods, smoking habits, histological type, Karnofsky performance status (KPS), and treatment modalities is made. The data collected by the authors suggest that nonsmokers formed the main group of lung cancer female patients. The most frequent histological type was adenocarcinoma. Mesothelioma was the most frequent of the secondary pulmonary lung cancers, followed from metastasizing breast cancer. Despite a generally good performance of the cases, the diagnosis of pulmonary cancer is delayed. The data collected could not find a convincing etiological role of tobacco smoking, but caution is needed, regarding the short time length of the study and the sustained number of participants.